2015
DOI: 10.2337/db15-0282
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Nesfatin-1 Stimulates Sympathetic Nerve Activity via Hypothalamic ERK Signaling

Abstract: Nesfatin-1 acts on the hypothalamus and regulates the autonomic nervous system. However, the hypothalamic mechanisms of nesfatin-1 on the autonomic nervous system are not well understood. In this study, we found that intracerebroventricular (ICV) administration of nesfatin-1 increased the extracellular signal-regulated kinase (ERK) activity in rats. Furthermore, the activity of sympathetic nerves, in the kidneys, liver, and white adipose tissue (WAT), and blood pressure was stimulated by the ICV injection of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
5
33
0
1
Order By: Relevance
“…It has also been reported that nesfatin-1 can stimulate the phosphorylation of AMP-dependent protein kinase (AMPK), Akt kinase (Akt) and target of rapamycin complex (TORC) 2, resulting in an increase in Fos immunoreactivity in the hypothalamic nuclei that mediate glucose homeostasis58. In accordance with our results, nesfatin-1 has also been reported to stimulate sympathetic nerve activity via hypothalamic ERK signaling59 and increased cAMP response element (CRE) reporter activity in a mouse neuroblastoma cells60. Further studies are required to determine which CRE-regulated genes are involved in the protective effects of nesfatin-1 on dopaminergic neurons.…”
Section: Discussionsupporting
confidence: 91%
“…It has also been reported that nesfatin-1 can stimulate the phosphorylation of AMP-dependent protein kinase (AMPK), Akt kinase (Akt) and target of rapamycin complex (TORC) 2, resulting in an increase in Fos immunoreactivity in the hypothalamic nuclei that mediate glucose homeostasis58. In accordance with our results, nesfatin-1 has also been reported to stimulate sympathetic nerve activity via hypothalamic ERK signaling59 and increased cAMP response element (CRE) reporter activity in a mouse neuroblastoma cells60. Further studies are required to determine which CRE-regulated genes are involved in the protective effects of nesfatin-1 on dopaminergic neurons.…”
Section: Discussionsupporting
confidence: 91%
“…Beyond these early studies that reported the effect of exogenous nesfatin-1 on BP, our results have revealed the endogenous NUCB2/nesfatin-1 in PVN as a regulator of preload of circulation through modulating PVN AVP. Alternatively, a recent study has reported that nesfatin-1 regulates the sympathetic nervous system through ERK signaling in PVN-CRH neurons to maintain cardiovascular function (33). In this line, we previously reported that NUCB2/nesfatin-1 is colocalized with CRH as well as oxytocin and AVP in PVN neurons (12).…”
Section: Discussionmentioning
confidence: 90%
“…Accordingly, no increase 232:1 in cyclic adenosine monophosphate (cAMP) formation was observed (Ishida et al 2012). Nevertheless, CREB phosphorylation was increased in a neuroblastoma cell line (Ishida et al 2012), however, not in vivo (Tanida et al 2015). The activation of protein kinase A (PKA) appears to differ across tissues and might indicate a tissue-specific recruitment of G-protein subunits (Brailoiu et al 2007, Nakata et al 2011, Ishida et al 2012.…”
Section: Nesfatin-1: Signal Transductionmentioning
confidence: 99%
“…These findings, albeit unequivocal with regard to the type of G-proteins involved, suggest the existence of one or more 7-transmembrane receptor(s). Furthermore, mitogen-activated protein kinases (MAPK) (extracellular signal-regulated kinase (ERK1/2)) (Ishida et al 2012, Angelone et al 2013, Tanida et al 2015 is activated by nesfatin-1; 5â€Č AMP-activated protein kinase (AMPK) and phosphatidylinositol-3-kinases (PI3K), however, do not appear to be involved (Tanida et al 2015).…”
Section: Nesfatin-1: Signal Transductionmentioning
confidence: 99%
See 1 more Smart Citation